Phenotypic and genotypic characterization of nonO1/ nonO139 Vibrio cholerae from aquaculture farm sediments - Reethy, P. S.; Lalitha, K. V. (Fishery Technology, 2020)
Toxigenic Vibrio cholerae is a major public health problem in developing countries andlysogenic conversion of naturally occurring nontoxigenic V. cholerae strains by a lysogenic filamentous bacteriophage CTXÃ– has also been demonstrated. The aim of this study was to analyse phenotypic and genotypic characteristics of V. cholerae strains from sediments in aquaculture settings. Based on biochemical, molecular and serological assays confirmed the presence of fourty nine nonO1/nonO139 V.cholerae strains from fifty six sediment samples. PCR assays revealed that all V.cholerae strains harboured toxR, hlyA and ompW genes. But none of the virulent genessuch as ctxA, tcpA, ace and zot were present in all tested strains. Antibiotic susceptibility to different antibacterial agents was also performed by disc diffusion assay. This result has shown 26.5% of the non-O1/non-O139 V.cholerae isolates were multidrug resistant for three classes of antibiotics. Genetic diversity of nontoxigenic V.cholerae isolated from aquaculture farm sedimentswas determined by ERIC PCR.The genetic diversity studies revealed clonal relationship among the various non-O1/non- O139 isolates.